Regulatory mechanism of trichothecene biosynthesis in Fusarium graminearum - Liew, Maydelene Xiao Xuan; Nakajima, Yuichi; Maeda, Kazuyuki; Kitamura, Naotsugu; Kimura, Makoto (Frontiers in Microbiology, 2023)
Among the genes involved in the biosynthesis of trichothecene (Tri genes), Tri6 and Tri10 encode a transcription factor with unique Cys2His2 zinc finger domains and a regulatory protein with no consensus DNA-binding sequences, respectively. Although various chemical factors, such as nitrogen nutrients, medium pH, and certain oligosaccharides, are known to influence trichothecene biosynthesis in Fusarium graminearum, the transcriptional regulatory mechanism of Tri6 and Tri10 genes is poorly understood. Particularly, culture medium pH is a major regulator in trichothecene biosynthesis in F. graminearum, but it is susceptible to metabolic changes posed by nutritional and genetic factors. Hence, appropriate precautions should be considered to minimize the indirect influence of pH on the secondary metabolism while studying the roles of nutritional and genetic factors on trichothecene biosynthesis regulation. Additionally, it is noteworthy that the structural changes of the trichothecene gene cluster core region exert considerable influence over the normal regulation of Tri gene expression. In this perspective paper, we consider a revision of our current understanding of the regulatory mechanism of trichothecene biosynthesis in F. graminearum and share our idea toward establishing a regulatory model of Tri6 and Tri10 transcription.